Generation mean analysis for seed yield and its related attributes in Pusa Gold x YST-151, Ragni x NDYS-425 and Ragni x YST-151 crosses of yellow sarson: GENERATION MEAN ANALYSIS IN YELLOW SARSON - AKANKSHA P K SINGH; O P VERMA; K KUMAR (Journal of Oilseeds Research, 2018)
Three cross combinations were attempted by using Pusa Gold, YST-151, Ragni and NDYS-425 cultivars of yellow sarson as parents. Parents were selected on the basis of variability for days to maturity, seed yield, oil contentand other agronomic traits. Six generations (P1, P2, F1, F2, BC1, BC2) in each cross (Pusa Gold x YST-151, Ragni x NDYS-425 andRagni x YST-151) were evaluated in a compact family block design with three replications during 2011-12 cropping season. Data were recorded for several morpho-physiological traits like seed yield per plant, plant height, primary branches per plant, Daysto 50% flowering, length of fruiting zone, siliqua per plant, siliqua length, days of maturity, 1000-seed weight and oil content. Analysis of variance for six generations revealed significant differences among the progenies (generations) within family (cross) for most ofthe evaluated traits except for siliqua length and days to maturity. The differences were highly significant (p#0.001) for length of fruiting zone and seed yield per plant. For the traits primary branches per plant, siliqua per plant and seed yield per plant, the performance of hybrids was superior to their respective parents in all crosses studied. Six parameter model (m, d, h, i, j, l) and scaling tests revealed the presence of inter-allelic interactions (epistasis) for most of evaluated traits except days to maturity in Pusa Gold x YST-151cross and indicated the inadequacy of additive-dominance model. The prime objective of current study was to estimate gene effects controlling yield and its related attributes by generation mean analysis and scaling test.